NUTRITIONAL QUALITY OF THE EGG MASS AS “LUKOT” OF THE WEDGE SEAHARE DOLABELLA AURICULARIA (LIGHTFOOT, 1786) - Pepito, Ador R.; Delan, Gloria G.; Asakawa, M; Ami, L J.; Yap, EE S; Olympia, MS D; Maningo, Aurelia G.; Rica, Rachel Luz V.; Lamayo, Roberto C.; Babaran, Monina C.; Abdon, Hector C. (Journal of Agriculture and Technology Management; Tropical Technology Journal Volume 17 No. 1, 2014, 2018)
The egg mass of the wedge seahare Dolabella auricularia has been gathered as human food for quite a long time without knowing its nutritional  composition. Thus, this study was conducted  in  order  to  determine  some  nutritional  aspects  of  the  egg  mass  as  basis  of  its utilization as human food. Important composition of the egg mass that were determined were its proximate composition, mineral contents and amino acid profile. In terms of proximate composition, the egg mass has a moisture content of 91.10 percent, fat of 0.85 percent, protein of 2.85 percent, ash of 3.43 percent and 1.77 percent for carbohydrates. The mineral content such as: calcium, iron, potassium, sodium and zinc contains 1040 mg/kg, 25.3 mg/kg, 599 mg/kg, 9803 mg/kg and 41.6 mg/kg, respectively. The amino acid profile, has six (6) essential amino acids such as: threonine, valine, isoleucine, leucine, phenylalanine and hstidine while it has nine (9) non-essential amino acid like: taurine, aspartic acid, serine, glutamic acid, glumatimine, glycine, alanine, tyrosine, proline. It has also eight (8) other amino acids components such as: Phospo - serine, urea, aromatic amino acid, citrulline, beta-alanine, gamma-aminobutyric acid, ammonia, ornithine.  Results  show  that  the  egg  mass  of  the  wedge  seahare  contains  some  nutritional components that are very essential in maintaining a healthy and balanced life, thus making it as another food commodity from the marine environment.